Campur Kode Bahasa Indonesia dan Bahasa Jawa Serang: Pola Penggunaan dan Partikel Khas jawa Serang - Tubagus Rahmat (Jurnal Silatene Sosial Humaniora, 2024)
This study aims to describe the mixed form of Indonesian and Javanese Serang codes and the causative factors. This study uses a qualitative description method with a descriptive approach. The data of this research is the speech of the people of Kasemen-Serang City. The results of the study show that (1) The form of Code Mixing is in the form of word insertion; (2) the factor of code mixing causes a sense of closeness and warmth in communication; (3) Javanese particles dominate spoken; and (4) Mixing Codes has a positive impact as an effort to defend regional languages.